Sudan: Cereal markets and trade - Dorosh, Paul A.; Kirui, Oliver K.; Siddig, Khalid (International Food Policy Research Institute, 2025)
Cereal production and markets, key components of Sudan’s food economy, have changed dramatically in the last decade due to conflict-related disruptions, as well as earlier changes in government policy. In western Sudan, particularly Darfur and surrounding regions, ongoing conflict has severely hindered agricultural activities, leading to a sharp decline in domestic cereal production. In contrast, other regions of Sudan have maintained relatively stable planting and harvesting activities, although marketing costs have risen substantially.